(Turnitin) Effect of Avocades to LDL Cholesterol as a Preventive Risk of Atherosclerosis - Shahrul Rahman (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Objective: Cardiovascular disease is the highest cause of death in most developing countries. Hypercholesterolemia, especially high LDL is a risk factor for cardiovascular disease can be overcome through a good diet. Avocado fat is included in healthy fats, because it is dominated by monounsaturated fatty acids oleate. Based on the description, it is necessary to do research on the effect of avocado juice on lipid profiles in humans Method: This study used a pre and post test only control group design research method to determine the effect of avocado juice on LDL cholesterol in humans. Before the study began (H-7) participants were asked not to consume avocados, then at the beginning of the study blood was taken to check for LDL cholesterol. After that, the study participants were given avocados made in the form of juice for 14 days to then check the LDL cholesterol again and compared the results Result: There was a statistically significant decrease in LDL cholesterol levels after giving avocado juice for 14 days with p 0.003 Conclusion: Avocado juice has a good effect that can decreased LDL cholesterol level and has a protective effect on the risk of atherosclerosis